2020
DOI: 10.1177/0887403420921232
|View full text |Cite
|
Sign up to set email alerts
|

Religious Duress and Reverential Fear in Clergy Sexual Abuse Cases: Examination of Victims’ Reports and Recommendations for Change

Abstract: According to prior research, approximately 14% of sexual victimizations by priests are reported to civil authorities. Victim grooming by the abuser is a main reason the number of reported incidents is low. The concept of reverential fear and religious duress is related to grooming, but very little empirical research focuses on the concept. Reverential fear and religious duress is a type of fear that limits the ability of clergy sexual abuse victims to disengage from their abuser; it intensifies when one has re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Benkert and Doyle (2009) suggested that as a consequence of their role within the religious hierarchy, victims of clergy-perpetrated CSA may experience reverential fear and religious duress which can influence the sexual grooming process. Spraitz and Bowen (2020) examined the use of religious duress and reverential fear in a sample of 51 clergy from three diocese who were accused of CSA. Overall, they coded 64 potential instances of religious duress and reverential fear as exhibited by 29 out of the 51 priests (57%).…”
Section: Sexual Grooming By Clergymentioning
confidence: 99%
See 3 more Smart Citations
“…Benkert and Doyle (2009) suggested that as a consequence of their role within the religious hierarchy, victims of clergy-perpetrated CSA may experience reverential fear and religious duress which can influence the sexual grooming process. Spraitz and Bowen (2020) examined the use of religious duress and reverential fear in a sample of 51 clergy from three diocese who were accused of CSA. Overall, they coded 64 potential instances of religious duress and reverential fear as exhibited by 29 out of the 51 priests (57%).…”
Section: Sexual Grooming By Clergymentioning
confidence: 99%
“…the sexual grooming process and the perpetration of CSA (Raine & Kent, 2019;Tishelman & Fontes, 2017), including having easy access to children and the ability to achieve implicit trust from their families (Spraitz & Bowen, 2020). Benkert and Doyle (2009) suggested that as a consequence of their role within the religious hierarchy, victims of clergy-perpetrated CSA may experience reverential fear and religious duress which can influence the sexual grooming process.…”
Section: Sexual Grooming By Clergymentioning
confidence: 99%
See 2 more Smart Citations
“…La culpa, como fenómeno complejo, se ve acentuada además por lo que Spraitz & Bowen (2021) han denominado como miedo reverencial y coacción religiosa, comentados previamente. En este escenario, además, las distorsiones cognitivas (de la Villa & González, 2020), comprendidas como un conjunto de ideas erróneas que operan como verdad en el sujeto que las cree, contribuyen a acentuar la culpa ya que la víctima se percibe en referencia al agresor como una persona que: a) provocó el abuso; b) permitió el abusoy no fue capaz de frenarlo; c) tiene responsabilidad ante el abuso y; d) debe sacrificarse con su silencio en pro de algo mayor y ese algo mayor es la Iglesia.…”
Section: Estrategias De Invisibilización Del Abusounclassified